Legal Construction of Sting Operations in the Emptiness of Criminal Procedure Norms - Sholihin, Ahmad; Cibro, Hamdani (Civiliza Publishing, 2025)
Hand-caught Operations (OTT) are a law enforcement practice frequently used to eradicate corruption, but their implementation has generated legal debate because they are not explicitly regulated in criminal procedural law. This study aims to analyze the legal construction of Hand-caught Operations in the absence of criminal procedural law norms and to assess their compliance with the principle of due process of law. The research method used is normative legal research with a statutory and conceptual approach. Legal materials are analyzed qualitatively through a review of criminal procedural law provisions, laws and regulations related to corruption eradication, and relevant legal doctrines. The results show that Hand-caught Operations are legally constructed through a broad interpretation of the concept of being caught red-handed, rather than based on firm procedural regulations. This condition creates legal uncertainty and has the potential to weaken the guarantee of protection of the suspect's rights. The study's conclusion confirms that although Hand-caught Operations have been effective in law enforcement practices, their sustainability requires clear procedural regulations to ensure legal certainty, justice, and the protection of human rights in the criminal justice system